Marble inspired coffee table / Athirah Izzati Razak - Razak, Athirah Izzati (2020)
Furniture is designed through various processes and materials which are heavily influenced the quality of the end product. The design of furniture in Malaysia nowadays are lack of creativeness and too simple. Furthermore, the shortage of raw materials for furniture production has affected the revolution of furniture designing which has led to the use of alternatives materials to replace wood. In this study, a Marble Inspired Coffee Table with modem elegant concept was manufactured using epoxy resin and Kelempayan to fulfil the needs of aesthetic and to counter the diminishing of raw material while adding multifunction feature to the product. After going through designing and manufacturing process, a survey was conducted to 103 respondents by randomly distributing a set of questionnaire that concerns with the characteristics of Marble Inspired Coffee Table. The result shows that there are no significant differences on the characteristics of the Marble Inspired Coffee Table based on the range of age. While, there are significant differences showed on the characteristic of the product based on gender which are the marble inspired appearance, aesthetic appearance and multifunction feature. There is also a highly significant on selling price characteristic of the product. Overall, Marble Inspired Coffee Table has successfully designed and manufactured by using epoxy resin and Kelempayan. It is also proven that it is well accepted by majority of the respondent regardless different gender and age.